Pengaruh Lingkungan Kelas Terhadap Prestasi Belajar Peserta Didik MTs Ma’arif NU 04 Desa Kladi Kecamatan Cermee Bondowoso - Lusy Endang Sri Darmawati; Tutik Anggraeni; Miftahus Surur (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
This study aims to determine whether there is an effect of the classroom environment on learning achievement. This research is a quantitative research. Methods of data collection using questionnaires or questionnaires, documentation and observation. The research subjects were all students at MTs Ma'arif NU 04 Kladi village with a total population of 60 students. Data analysis includes correlation and variation of the regression line. Hypothesis testing to determine the effect of the classroom environment on student learning achievement with the results of F count = 129,315, F table 3,16 at = 0,05 turns F count = 129,315 > f table 3,16 Effective contribution (SE) predictor (X_1) environment physical class to the criterion (Y) of student learning achievement 29.843.493%. Effective contribution ( SE) predictor ( X_2) non-physical classroom environment on student learning achievement 29.036%, this indicates that the physical and non-physical classroom environment affects student learning achievement. With the results of the data that have been described previously, it can be said that